USAHATANI CABAI PADA KELOMPOK TANI WASIAN TUMAWOY DI TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA (Chili Farming of the Wasian Tumawoy Farmer Group in Tombasian Atas Kawangkoan Barat District, Minahasa Regency) - Christian M. Mamoto; Jenny Baroleh; Noortje M. Benu (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The purpose of this study was to analyze the chili farming based on the profit of one growing season in the Wasian Tumawoy Farmer Group in Tombasian Atas Village, Kawangkoan Barat District, Minahasa Regency. The research was carried out for three months, from October to December 2019. Data were collected through intervi ws with all 15 members of the Wasian Tumawoy Farmer Group (Chairperson, Secretary, Treasurer and farmer group members). The results showed that prices prevailing at the farmer group level varied, where the highest price reached Rp. 35,000 / kg and the lowest price was Rp. 15,000 / kg. It could be concluded the average profit of the farmer group was Rp. 31,620,000, in one harvest season (3 to 4 months). Keywords: Selling Price, Profits, Chili